2006
DOI: 10.1007/s10354-006-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for malignant gliomas

Abstract: Concomitant and adjuvant treatment with Temozolomide, an oral alkylating agent, has significantly improved the survival of patients with newly diagnosed glioblastoma multiforme (study EORTC 26981/22981, NCIC CE3). When given with the appropriate cautiousness including weekly clinical and laboratory controls during the concomitant phase, this therapy is generally well tolerated. The observed toxicity is mainly haematological. Grade III and IV toxicities mainly thrombocytopenia or lymphocytopenia occur in around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Qq-plots of peak torque of knee extensor muscles showed marked deviations from normal distribution. Therefore, Wilcoxon signed rank tests were performed to compare patients to expected values survive longer [1,2,[26][27][28][29]. Nevertheless, many of these patients are suffering from muscle weakness, fatigue, and rapid exhaustion in the early course of disease and probably related to the prescription of dexamethasone against increased cranial pressure [4][5][6][7][8]30].…”
Section: Discussionmentioning
confidence: 99%
“…Qq-plots of peak torque of knee extensor muscles showed marked deviations from normal distribution. Therefore, Wilcoxon signed rank tests were performed to compare patients to expected values survive longer [1,2,[26][27][28][29]. Nevertheless, many of these patients are suffering from muscle weakness, fatigue, and rapid exhaustion in the early course of disease and probably related to the prescription of dexamethasone against increased cranial pressure [4][5][6][7][8]30].…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of α- (1,4-) naphthoquinone compound, plumbagin has a wide range of biological activities. In recent years, it has been found that plumbagin can inhibit the proliferation of breast cancer, lung cancer, osteosarcoma, liver cancer, leukemia, ovarian cancer and other tumor cells, which shows its good anti-tumor prospects and has attracted extensive attention [4][5][6][7] . Previous studies have shown that plumbagin can inhibit the proliferation of glioma cells and induce the apoptosis process.…”
mentioning
confidence: 99%
“…In addition, TMZ treatment is fraught with side effects, such as hematological toxicity, vomiting, fatigue, and nausea. 4 Further, many GBM patients develop resistance to the drug. 5,6 There is thus a need to identify novel strategies for pharmacological treatment with improved efficacy, lower variability across patients, reduced rate of resistance development, and fewer side effects.…”
mentioning
confidence: 99%